Identification And Correction Of Pseudowords In Ilman Wa Ruhan Textbooks To Reduce Meaning Errors/ التعرف على الألفاظ الزائفة وتصحيحها في الكتاب المدرسي علما وروحا للحد من المعاني الخاطئة - Jundi, Ahmad; Baihaqi, M; Zaenuri, Muh; D., Habib; Solihah, Iis; Fatihuddin, Fatihuddin; Kharolina, Kharolina (Ijaz Arabi Journal of Arabic Learning, 2025)
The existence of pseudo-words in textbooks is a serious problem and requires special attention. This will certainly have a negative impact on the quality of learning and the achievement of educational goals. This research aims to reveal teaching materials that are pseudo and provide corrections to these materials so that they become more meaningful and useful for learners. This paper uses an adaptation of the qualitative content analysis method, namely identifying, and classifying. The data was obtained through direct observation of Ilman wa ruhan volume one and two textbooks that enter the word learning process. The observation instrument of this research is maany digital dictionary which has been standardized internationally. The conclusion of this study shows the existence of pseudo-words in volume one and volume two textbooks in the early part of learning three connected letters. The research findings revealed the existence of 24 pseudo-words in the form of three kinds of criteria, namely the criteria for vocal incompatibility, consonant incompatibility criteria and writing incompatibility criteria.  This study contributes to the correction of these pseudo-words so that the learners read and pronounce the correct language in Arabic and the Koran. This effort is expected to improve the quality of textbooks and support the creation of a meaningful learning process for students.